2018
DOI: 10.7717/peerj.4691
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic venom proteins in long-jawed orb-weaving spiders (Tetragnatha) comprise novel gene families

Abstract: Venom has been associated with the ecological success of many groups of organisms, most notably reptiles, gastropods, and arachnids. In some cases, diversification has been directly linked to tailoring of venoms for dietary specialization. Spiders in particular are known for their diverse venoms and wide range of predatory behaviors, although there is much to learn about scales of variation in venom composition and function. The current study focuses on venom characteristics in different sexes within a species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
(58 reference statements)
0
22
0
Order By: Relevance
“…To what extend a specialization on one type of prey affects the composition of the venom is largely uninvestigated in spiders. However, a certain heterogeneity between venoms of individuals of the same species depending on age, gender, or geographic location has been reported and supports a possible adaptation of the venom composition [34,35]. Adaptive evolution of venom components on prey is described for other venomous animals, such as snakes [36,37,38], and cone snails [39,40].…”
Section: Spider Venom Compositionmentioning
confidence: 99%
“…To what extend a specialization on one type of prey affects the composition of the venom is largely uninvestigated in spiders. However, a certain heterogeneity between venoms of individuals of the same species depending on age, gender, or geographic location has been reported and supports a possible adaptation of the venom composition [34,35]. Adaptive evolution of venom components on prey is described for other venomous animals, such as snakes [36,37,38], and cone snails [39,40].…”
Section: Spider Venom Compositionmentioning
confidence: 99%
“…Sexual variation of venom composition has been documented for a few taxa, principally spiders, scorpions, snakes, and a species of fish [ 122 , 123 , 124 , 125 ]. Research on Thalassophyrne maculosa (cano toadfish) showed that male venom had double the protein content of that of females and differing bioactivities, with males having a greater target affinity to nociceptors whilst females had greater proteolytic activity [ 123 ].…”
Section: Intersexual Variation In Venommentioning
confidence: 99%
“…The advances in sensitivity and resolution of mass spectrometers as well as advances in DNA and RNA sequencing techniques have led to a remarkable increase in the number of toxins reported in the last years (Duan et al, 2013;Sanggaard et al, 2014;Zelanis and Keiji Tashima, 2014;Abreu et al, 2017;Zobel-Thropp et al, 2018;Langenegger et al, 2019). However, the increase in toxin identification is not synchronized with the functional description of new toxins, since the functional characterization involves a significant number of experimental processes.…”
Section: Introductionmentioning
confidence: 99%